IMPLEMENTASI TATANEN DI BALE ATIKAN DALAM PEMBELAJARAN PADA MATERI SURAT IBRAHIM AYAT 32 - saepul, eep (MGMP PAI Jawa Barat, 2023)
This study aims to investigate the implementation of Bale Atikan in learning the material of Surah Ibrahim verse 32 by using descriptive research method. Bale Atikan is a learning approach that emphasizes the use of well-organized and comfortable physical spaces to create a conducive learning environment. This research involves a group of students learning about Surat Ibrahim verse 32 in a room that has been arranged according to the principles of order in Bale Atikan. Descriptive research method was used to describe in detail how the implementation of order in Bale Atikan affects the learning process and students' understanding of the material of Surah Ibrahim verse 32. Data were collected through observation, interviews, and analysis of related documents. The results show that the implementation of order in Bale Atikan can create a more conducive learning environment and make it easier for students to understand and internalize learning materials. This research contributes to understanding the role of order in Bale Atikan in improving learning effectiveness, especially in the context of Islamic learning. The practical implication of this research is that the use of Bale Atikan arrangements can be an effective alternative in designing classrooms that facilitate understanding and appreciation of religious material. This research can also serve as a foundation for further development in utilizing the principles of order in Bale Atikan in other learning contexts. Keywords: Implementation, Practical, Process